Data files for Low-Cost Textile Myoelectric Control of KAFO paper - Pitou, Samuel (King's College London, 2019)
The use of surface electromyography (sEMG) for the detection of heel-strike and toe-off is investigated in order to control the knee joint of passive KAFOs. This has the potential to allow for the knee joint to bend during the swing and to lock during the stance of the supported leg. sEMG and motion capture experiments are run in India on three healthy participants were they are asked to perform a normal gait in a straight direction. These experiments are performed with embroidered electrodes which are a low-cost and reusable alternative to disposable gel electrodes. The event to predict are heel-strike and toe-off from the rest of the gait.
Keywords: EMG, Motion Capture, Healthy subjects